Referential multimodality in “animated documentaries” and “documentary games” - Thon, Jan-Noël (Duke University Press, 2018)
From John Grierson’s influential early definition of documentary as “the creative treatment of actuality” through documentary studies’ reconstruction of the multitude of existing forms to philosophers’ attempts to develop comprehensive accounts of documentary as a specific kind of nonfiction film, the concept of documentary has been both fiercely contested and, through these debates, continuously expanded to refer to an ever more extensive corpus of works. By now, there is a broad consensus that documentary film as a genre cannot be reduced to supposedly “objective” recordings of the “actual world,” as both various kinds of reenactments and sometimes radical forms of subjectivity have (yet again) become well-established elements of many documentary films. However, it would seem that summarily treating “hybrid” documentary films, “animated documentaries,” and “documentary games” as nothing but the most recent chapter of the history of documentary occludes more than it illuminates. Instead, this article proposes to examine “animated documentaries” such as Chicago 10: Say Your Peace (Brett Morgen, 2007) or Waltz with Bashir (Ari Folman, 2008) and “documentary games” such as JFK Reloaded (Traffic Games, 2004) or The Cat and the Coup (Peter Brinson and Kurosh ValaNejad, 2011) through the lens of post/documentary, thus emphasizing not just their semiotic but also their occasionally rather complex referential multimodality.